Popular culture in Europe since 1800 - Becker, Tobias, author.
1 online resource
Keywords: "This book tells the story of the history of popular culture in Europe since 1800, providing a framework which challenges traditional associations that have formulated popular culture firmly in relation to the post-1945 period and the economic power of the USA. Focusing on key themes associated with modernity - secularization, industrialization, social cohesion and control, globalization and technological change - this synthesis of research across a very wide field fills a gap that has long been felt by students and educators working in the field of popular culture. While it is organized as a history of cultural forms, it can also be used across a wide range of social science and humanities programmes, including media and cultural studies, literary studies, sociology and European studies. Covering the subject with a broad number of themes, this book discusses popular culture through visual culture and performance, games, music, film, television, and video games. Popular Culture in Europe since 1800 will be of interest to anyone looking for an engaged but concise overview of how book production and reading practices, visual cultures, music, performance and sports and games developed across Europe in the modern period"--